INTEGRATION OF EMPLOYEE PERFORMANCE, SERVICE QUALITY, ARTIFICIAL INTELLIGENCE, AND SOCIAL MEDIA IN INCREASING PATIENT NUMBERS: A SYSTEMATIC LITERATURE REVIEW - Irawan, Beny; Mochklas, Mochamad; Haksama, Setya (Yayasan Nuraini Ibrahim Mandiri, 2025)
This literature review analyzes and synthesizes the relationship between employee performance, service quality, the use of artificial intelligence (AI), and the use of social media in efforts to increase patient numbers in the healthcare sector. Using a systematic literature review approach, this research examines various studies that discuss the contribution of each variable to increasing patient accessibility and interest. A total of 20 empirical journal articles published between 2018 and 2024 were analyzed thematically. Data were collected from various academic databases using keywords such as